The effect of rosemary, ginger, or garlic on microbial shelf life and sensory acceptability of nutritionally enriched cassava-based pancake (Kabalagala) - Mahoussi Simone Assocle; Lawrence Okidi; Duncan Ongeng (Applied Food Research, 2024)
Iron and vitamin A contents of Cassava-based pancake (Kabalagala), a delicacy among children in northern Uganda have recently been improved through the addition of biofortified iron-rich beans and orange-fleshed sweet potato. The nutritionally improved product (NIK) was designed as a strategy to address iron and vitamin A deficiencies which are endemic challenges among children in Uganda. However, the NIK had a lower microbial shelf life (24 h) than the original product (72 h). The objective of this study was to investigate the potential of the spices; rosemary, ginger, and garlic to improve the microbial shelf life of the NIK. Each of the spices was used individually to prepare NIK at a rate of 0.5, 0.75, and 1 %. The resultant products were evaluated for counts of total microbial load, Enterobacteriaceae, lactic acid bacteria, yeasts and molds as well as consumer sensory acceptability during storage at ambient temperature. Results of One-way Analysis of Variance (ANOVA) showed that all the spices exhibited potency against the microbial groups investigated only when included in the NIK at 0.75 % or 1 % (p < 0.05). The microbial shelf life of the NIK based on total microbial count increased from 24 to 72 h depending on the spice type and concentration. The spice, 1 % ginger resulted in Enterobacteriaceae and yeast and molds counts within acceptable microbial threshold for the entire storage time (72 h) with a maximum load of 3.41 and 2.82 log10 CFU/g, respectively. The NIK containing ginger or garlic at 0.75 or 1 %, was more accepted and the extent of acceptability increased with storage time (p < 0.05). Based on the overall acceptability, the consumer acceptability varied from 1 % garlic >0.75 % garlic >1 % ginger >0.75 % ginger >0.5 % ginger in decreasing order. Spearman's correlation analysis revealed a strong association between the sensory parameters examined (appearance, aroma, texture, taste) and the overall acceptability of the products (p < 0.05). The magnitude of association between appearance, aroma, texture, taste and overall acceptability varied between 0.396–0.703, 0.504–0.679, 0.452–0.589, and 0.498–0.698, respectively. This study has demonstrated that ginger or garlic when applied at 0.75–1 % improves microbial shelf life of NIK concomitant with better consumer sensory acceptability. Therefore, ginger or garlic can be applied at 0.75–1 % to produce microbiologically and sensorially acceptable NIK for use to improve intake of vitamin A and iron among children in Uganda.